Older Peoples' Adherence and Awareness of Changes in Drug Therapy after Discharge from Hospital - Sara Norberg; Maria Gustafsson (MDPI AG, 2018)
Non-adherence is important to address because it might affect the effectiveness of therapy and lead to adverse effects. The objectives of this interview study were to investigate old peoples’ general adherence to drugs and their awareness of and adherence to changes in drug therapy after their hospital stay. Following ethical approval, 42 patients admitted to the medical ward were invited to participate in this study. Of these, 36 persons, with a mean age of 82.5 years, who were discharged to their home, were interviewed by telephone using the Medical Adherence Report Scale (MARS) to assess their general adherence to prescribed drugs. Questions regarding awareness and adherence to drug changes during their hospital stay were asked. Different factors related to adherence and non-adherence were investigated using the Pearson chi-square test and the independent sample t-test. The average MARS score was 23.9 ± 1.4, with 31 persons (86%) assessed as adherent to their drug therapy and 5 persons (14%) as non-adherent. Of the 36 people, 30 had at least one change in their drug therapy during their hospital stay, and 23 (77%) of these people were aware of all changes and 23 (77%) were adherent to all of the changes. No significant differences between adherence and age, gender, living situation, or number of drugs were found. This small study found that some older people who were discharged from hospital were generally non-adherent, and some were not aware of or adherent to changes made in the drug therapy during their hospital stay. This is an important problem to address with further interventions.